A DNA Biometric Implementation Model to Promote Thailand’s Criminal Justice System - Wisarn Worasuwannarak; Suppakorn Poonyarith; Sunee Kanyajit; Veenunkarn Rujipak; Worawee Waiyawuth (Science & Technology Asia, 2025)
DNA biometrics has proven to be a valuable tool in criminal justice systems worldwide, providing accurate identification and helping solve crimes effectively. However, Thailand faces several challenges in implementing DNA biometrics in its criminal justice system. This study aimed to explore the use of DNA as reliable biometric data in Thailand’s judicial and authentication processes, develop operational procedures for practical use, identify problems and obstacles, and propose a suitable model for implementation. The study employed documentary research and in-depth interviews with sixteen experts in the criminal justice system. The findings revealed that the absence of a central authority for collecting DNA biometric data results in disparate management of DNA databases and a lack of coordination between agencies. Personnel and budget issues, insufficient professional standards for forensic science officers, and the absence of a central agency responsible for forensic science work management also hinder Thailand’s forensic science operations. Issues related to crime scene protection, such as the lack of operational guidelines for collecting evidence and insufficient first-response units, were also identified. Furthermore, Thai judges often lack sufficient knowledge to assess the reliability of forensic evidence. Another major obstacle is the absence of a law to establish a central agency that administers the National DNA Database. The study proposes the establishment of a central agency to oversee the collection and management of DNA biometric data, the development of clear operational guidelines, and the provision of training for personnel involved in the criminal justice system to effectively implement DNA biometrics in Thailand.